Tetrahydrobiopterin, its mode of action on phenylalanine hydroxylase, and importance of genotypes for pharmacological therapy of phenylketonuria - Heintz, Caroline; Cotton, Richard G. H.; Blau, Nenad (Human mutation, 2013)
In about 20%-30% of phenylketonuria (PKU) patients (all phenotypes of PAH deficiency), Phe levels may be controlled through phenylalanine hydroxylase cofactor tetrahydrobiopterin therapy. These patients can be diagnosed by an oral tetrahydrobiopterin challenge and are characterized by mutations coding for proteins with substantial residual PAH activity. They can be treated with a commercially available synthetic form of tetrahydrobiopterin, either as a monotherapy or as adjunct to the diet. This review article summarizes molecular and metabolic bases of PKU and the importance of the tetrahydrobiopterin loading test used for PKU patients. On the basis of in vitro residual PAH activity, more than 1,200 genotypes from patients challenged with tetrahydrobiopterin were categorized as predictive for tetrahydrobiopterin responsiveness or non-responsiveness and correlated with the loading test, phenotype, and residual in vitro PAH activity. The coexpression of two distinct PAH mutant alleles revealed possible dominance effects (positive or negative) by one of the mutations on residual activity as result of interallelic complementation. The treatment of the transfected cells with tetrahydrobiopterin showed an increase in residual PAH activity with several mutations coexpressed.